Internet Celebrity, Digital Illustration and Tradition: Rethinking Cultural Product Design for the Contemporary Age - You Xuemin; Rafeah Legino (Institut Seni Indonesia Yogyakarta, 2025)
This study explores the integration of traditional Chinese culture with digital illustration and internet celebrity influence to enhance contemporary promotional strategies. Focusing on the Weibo campaign for the